Kombinasi Transcutaneus Electrical Nerve Stimulation dan Integrated Neuromuscular Inhibition Technique untuk Menurunkan Nyeri dan Meningkatkan Kemampuan Fungsional Pasien dengan Hernia Nukleus Pulposus Lumbal - Sudaryanto Sudaryanto; Rahmat Nugraha; Hasbiah Hasbiah; Tiar Erawan; Aya Aimal Syaqshana (FORIKES, 2024)
Herniated nucleus pulposus can press on nerves or spinal cord, causing pain and spinal cord dysfunction. This study aimed to determine the effectiveness of the combination of Transcutaneous Electrical Nerve Stimulation and Integrated Neuromuscular Inhibition Technique to reduce pain and improve functional ability in patients with lumbar herniated nucleus pulposus. The method used in this study was a case report, involving two patients with lumbar herniated nucleus pulposus who met the criteria, namely patients with grade 1-2 lumbar herniated nucleus pulposus, not accompanied by severe stenosis of the spinal canal, not obese, and experiencing bulging in the L4-S1 area. Transcutaneous Electrical Nerve Stimulation and Integrated Neuromuscular Inhibition Technique were given 8 times. Measurement of pain levels was carried out using the Visual Analog Scale and measurement of functional ability was carried out using the Patient Specific Functional Scale. Furthermore, the data were analyzed descriptively. The results of the study showed that patient I experienced a decrease in silent pain from 3 to 0, tenderness from 6 to 1, and motion pain from 7 to 2, then experienced an increase in functional ability from 16 to 29; while patient II experienced a decrease in silent pain from 3 to 0, tenderness from 6 to 1, and motion pain from 8 to 3, then experienced an increase in functional ability from 14 to 25. Furthermore, it was concluded that the combination of Transcutaneous Electrical Nerve Stimulation and Integrated Neuromuscular Inhibition Technique can reduce pain and increase the functional ability of patients with lumbar hernia nucleus pulposus.Keywords: lumbar hernia nucleus pulposus; pain; functional ability; Transcutaneous Electrical Nerve Stimulation; Integrated Neuromuscular Inhibition Technique ABSTRAK Hernia nukleus pulposus dapat menekan saraf atau sumsum tulang belakang sehingga menyebabkan nyeri dan disfungsi sumsum tulang belakang. Studi ini bertujuan untuk mengetahui efektivitas kombinasi Transcutaneus Electrical Nerve Stimulation dan Integrated Neuromuscular Inhibition Technique untuk menurunkan nyeri dan meningkatkan kemampuan fungsional pasien dengan hernia nukleus pulposus lumbal. Metode yang digunakan pada studi ini adalah case report, yang melibatkan dua pasien dengan hernia nukleus pulposus lumbal yang memenuhi kriteria yaitu penderita hernia nukleus pulposus lumbal grade 1-2, tidak disertai dengan stenosis berat kanal spinal, tidak mengalami obesitas, dan mengalami bulging pada area L4-S1. Transcutaneus Electrical Nerve Stimulation dan Integrated Neuromuscular Inhibition Technique diberikan sebanyak 8 kali intervensi. Pengukuran tingkat nyeri dilakukan dengan menggunakan Visual Analog Scale dan pengukuran kemampuan fungsional dilakukan dengan menggunakan Patient Specific Functional Scale. Selanjutnya data dianalisis secara deskriptif. Hasil studi menunjukkan bahwa pasien I mengalami penurunan nyeri diam dari 3 menjadi 0, nyeri tekan dari 6 menjadi 1, dan nyeri gerak dari 7 menjadi 2, kemudian mengalami peningkatan kemampuan fungsional dari 16 menjadi 29; sedangkan pasien II mengalami penurunan nyeri diam dari 3 menjadi 0, nyeri tekan dari 6 menjadi 1, dan nyeri gerak dari 8 menjadi 3, kemudian mengalami peningkatan kemampuan fungsional dari 14 menjadi 25. Selanjutnya disimpulkan bahwa kombinasi Transcutaneus Electrical Nerve Stimulation dan Integrated Neuromuscular Inhibition Technique dapat menurunkan nyeri dan meningkatkan kemampuan fungsional pasien dengan hernia nukleus pulposus lumbal. Kata kunci: hernia nukleus pulposus lumbal; nyeri; kemampuan fungsional; Transcutaneus Electrical Nerve Stimulation; Integrated Neuromuscular Inhibition Technique